2022
DOI: 10.1177/03795721221123870
|View full text |Cite
|
Sign up to set email alerts
|

Training to Build Nutrition Capacity in the Nigerian Agricultural Sector: Initial Assessment and Future Directions

Abstract: Background: In response to calls to increase nutrition-sensitive agriculture (NSA), the Federal Ministry of Agriculture and Rural Development developed the Nigeria Agricultural Sector Food Security and Nutrition Strategy 2016-2025 (AFSNS). Capacity development activities to facilitate the AFSNS implementation subsequently commenced. Objective: This study analyzed the processes and outputs of initial capacity development efforts, examined findings from the analysis using existing literature, and identified crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…48 Still, the decrease in budgetary allocations to the Nutrition Division from 2018 to 2020 is of particular concern because it might be due to inadequate spending by the Nutrition Division in 2017. Several authors have highlighted that implementation of the AFSNS has been inadequate, [49][50][51] not just because of inadequate funding, but because of insufficient capacities to implement. 49 Nigeria used incremental budgeting in preparing budgets up until 2016.…”
Section: Discussionmentioning
confidence: 99%
“…48 Still, the decrease in budgetary allocations to the Nutrition Division from 2018 to 2020 is of particular concern because it might be due to inadequate spending by the Nutrition Division in 2017. Several authors have highlighted that implementation of the AFSNS has been inadequate, [49][50][51] not just because of inadequate funding, but because of insufficient capacities to implement. 49 Nigeria used incremental budgeting in preparing budgets up until 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Capacity development efforts at federal and state levels were, therefore, conducted in 2017. However, as is described in the study by Adeyemi et al 36 in the Special Issue, and summarized in the capacity section below, the capacity development efforts did not have the immediate outcomes anticipated and discussions commenced around the preparation of an Agricultural Sector Nutrition Workforce Capacity Development Strategy. Initial steps in such a Strategy include an understanding of the nutrition capacity needs of each cadre of workers expected to have a role in implementing NSA and food systems.…”
Section: Implementation Researchmentioning
confidence: 99%
“…The budget analysis reported in this Special Issue 33 13 into livelihoods projects to transform rural economies; and piloting the field collection of diet quality data using the DQQ. As highlighted by authors in the Special Issue, 36 inadequate capacity has been a major limiting factor for implementing and scaling up interventions.…”
Section: Financial Resource Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the trainings significantly increased their knowledge, large knowledge gaps remained and the ability of participants to implement nutrition-sensitive agriculture appeared inadequate. 9 Previous authors 10 reported that training is inefficient when contextually defined competencies required of participants have not been articulated apriori. Mucha and Tharaney 11 highlight the need for a systematic approach to nutrition capacity building, including the development of a Nutrition Workforce Strategy and Implementation Plan.…”
Section: Introductionmentioning
confidence: 99%